COMPREHENSIVE USE OF AQUAFITNESS EQUIPMENT IN HEALTH CLASSES FOR WOMEN AGED 35-40 (Scientific journal of the Fergana State University, 2025)
The article explores the comprehensive use of aqua fitness in the health training of women aged 35 to 40 years. The authors consider the effect of aqua aerobics, water gymnastics, swimming and other types of training conducted in water on the physical condition and general health of women in this age group. The results of the study show a positive effect of aqua fitness on strengthening muscles, improving flexibility and coordination of movements, as well as on the general well-being and psycho-emotional state of the training participants.